Women and Intertextuality: On the Example of Margaret Atwood’s The Penelopiad - Lisowska, Katarzyna (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2014)
The aim of the study is to consider feminist retellings of myths and legends. As an example, Margaret Atwood’s book The Penelopiad is analyzed. The interpretation is situated in a broader context of intertextual practices characteristic of the feminist vision of literature. I present the ideas which Atwood shares with authors engaged in women’s movement. Among these there is Atwood’s understanding of intertextuality (noticeable especially in The Penelopiad). Bibliographical basis of the study comprises books which are fundamental to feminist and gender criticism (e.g. Poetics of Gender, ed. by N. Miller, New York 1986; S. M. Gilbert, S. Gubar The Madwoman in the Attic. The Woman Writer and the Nineteenth- Century Literary Imagination, New Haven and London 1984). What is more, the study refers to the books which allow considering the notion of intertextuality (G. Allen, Intertextuality, London and New York 2010, J. Clayton. E. Rothstein (eds.), Influence and Intertextuality in Literary History, Wisconsin 1991) and connecting the interpretation with the problems crucial to contemporary literary studies (L. Hutcheon L. A Poetics of Postmodernism. History, Theory, Fiction, New York and London 1988, B. Johnson, A World of Difference, Baltimore and London 1989).